Phase separation on cell surface facilitates bFGF signal transduction with heparan sulphate - Song Xue; Fan Zhou; Tian Zhao; Huimin Zhao; Xuewei Wang; Long Chen; Jin-ping Li; Shi-Zhong Luo (Nature Communications, 2022)
Liquid-liquid phase separation (LLPS) is reported to occur in the intracellular environment. Here the authors show that heparan sulphate serves as a platform for basic fibroblast growth factor to undergo LLPS on the cell surface, therefore facilitating downstream signalling